Pseudomonas syringae pv actinidiae on surfaces in the orchard - Everett, K.R.; Pushparajah, I.P.S.; Vergara, M.J. (New Zealand Plant Protection, 2012)
A kiwifruit orchard that had tested positive for virulent Pseudomonas syringae pv actinidiae (PsaV) ca 2 km from the incursion detected in November 2010 was sampled on 13 December 2011 when the weather was overcast with some showers Surfaces on people (hands soles of footwear clothing) vehicles (tyres seats floors steering wheels accelerators brakes and gear levers) cleaned tools (shovels tip squeezers various handles drill bit) and rabbit feet were rubbed with sterile cotton wool medical swabs After incubation in bacterial growth medium DNA was extracted and samples tested in realtime PCR with primers that detect Psa Vehicle tyres the upright front of a trailer towed behind a vehicle and rabbit feet were the surfaces most frequently contaminated with Psa The surfaces contaminated with Psa were also those that were contaminated with soil demonstrating the importance of removing soil from implements vehicles and clothing on infected kiwifruit orchards before using liquid sanitisers